Surgical Antimicrobial Prophylaxis in Neonates and Children with Special High-Risk Conditions: A RAND/UCLA Appropriateness Method Consensus Study - Sonia Bianchini; Erika Rigotti; Laura Nicoletti; Sara Monaco; Cinzia Auriti; Elio Castagnola; Guido Castelli Gattinara; Maia De Luca; Luisa Galli; Silvia Garazzino; Stefania La Grutta; Laura Lancella; et al. (MDPI AG, 2022)
Surgical site infections (SSIs), which are a potential complications in surgical procedures, are associated with prolonged hospital stays and increased postoperative mortality rates, and they also have a significant economic impact on health systems. Data in literature regarding risk factors for SSIs in pediatric age are scarce, with consequent difficulties in the management of SSI prophylaxis and with antibiotic prescribing attitudes in the various surgical procedures that often tend to follow individual opinions. The lack of pediatric studies is even more evident when we consider surgeries performed in subjects with underlying conditions that may pose an increased risk of complications. In order to respond to this shortcoming, we developed a consensus document to define optimal surgical antimicrobial prophylaxis (SAP) in neonates and children with specific high-risk conditions. These included the following: (1) colonization by methicillin-resistant Staphylococcus aureus (MRSA) and by multidrug resistant (MDR) bacteria other than MRSA; (2) allergy to first-line antibiotics; (3) immunosuppression; (4) splenectomy; (5) comorbidity; (6) ongoing antibiotic therapy or prophylaxis; (7) coexisting infection at another site; (8) previous surgery in the last month; and (9) presurgery hospitalization lasting more than 2 weeks. This work, made possible by the multidisciplinary contribution of experts belonging to the most important Italian scientific societies, represents, in our opinion, the most up-to-date and comprehensive collection of recommendations relating to behaviors to be undertaken in a perioperative site in the presence of specific categories of patients at high-risk of complications during surgery. The application of uniform and shared protocols in these high-risk categories will improve surgical practice with a reduction in SSIs and consequent rationalization of resources and costs, as well as being able to limit the phenomenon of antimicrobial resistance.